Who cares for nutrition information at a restaurant? Food-related lifestyles and their association to nutrition information conscious behaviors. Issue 7 (4th July 2016) - Choi, Jinkyung
Abstract : Purpose: – People have become more health conscious about the food they eat on any occasion. As healthy dietary information has been released to the public in order to correspond with active public adaptation, more consumers have become aware of and are showing interest in new information related to health. The purpose of this paper is to utilize food-related lifestyle (FRL) instruments to explain nutrition information-conscious behaviors. Design/methodology/approach: – This study used a cross-sectional survey design. A questionnaire was developed based on previous studies. A factor analysis and a cluster analysis were conducted to segment nutrition information-conscious behaviors of consumers. Participants were 200 and the survey was administered to citizens in South Korea. Exploratory factor analysis, cluster analysis, analysis of variance, Duncan's multiple comparison tests, and χ 2 test were used. Findings: – Nine factors were identified and four clusters were established. These clusters were named: "personal value concern group, " "enthusiastic group, " "moderation group, " and "unconcerned group." Each segment was significantly different in body satisfaction and nutrition information-conscious behaviors. Nutrients such as dietary fibers, sodium, and trans fat were considered differently by the four segments. Originality/value: – Using an FRL instrument in relation to nutrition information-conscious behavior, interesting conclusions were drawn. Results of this study suggested that each segment has its characteristics in relation to nutrition information-conscious behaviors. Also it can be concluded that it is time for individuals to take responsibility for their own health problems.